ANALYSIS OF CK (CONTENT KNOWLEDGE) OF PRE-SERVICE BIOLOGY TEACHERS ON CONCEPT OF GENETICS AND ECOLOGY - Mega Elvianasti (Universitas Sultan Ageng Tirtayasa, 2018)
Content Knowledge (CK) is an ability to reveal a particular object based on the characteristics possessed by the object. The purpose of this research was to analyze the ability of Content Knowledge (CK) of Pre-service Biology Teachers to be viewed based on concept comprehension test. The study used qualitative methods, measured by giving a test in the form of a description of the genetics and ecology, the questions were compiled based on Bloom's taxonomy Revision from C2-C4 level. The research show that; in general prospective teachers have low mastery on the concept of gene regulation, Mendel's Law, and protein synthesis, but they have a good concepts on comprehension of Genes, DNA, and chromosomes, mutations, DNA relations, RNA, polypeptides, transcription and translation in the function of the formation of the nature of living things, and the relationship between sexual reproduction and gene inheritance. For the concept of ecology, in general they have a low mastery on the concept of interaction between organisms, biomass, community of organisms and global changes. While they have a good mastery on concept of the food chain system and the flow of energy, and the population.